Monitoring of SARS-CoV-2 in wastewater: what normalisation for improved understanding of epidemic trends?. (14th March 2022) - Sakarovitch, Charlotte; Schlosser, Olivier; Courtois, Sophie; Proust-Lima, Cécile; Couallier, Joanne; Pétrau, Agnès; Litrico, Xavier; Loret, Jean-François
Abstract: SARS-CoV-2 RNA quantification in wastewater has emerged as a relevant additional means to monitor the COVID-19 pandemic. However, the concentration can be affected by black water dilution factors or movements of the sewer shed population, leading to misinterpretation of measurement results. The aim of this study was to evaluate the performance of different indicators to accurately interpret SARS-CoV-2 in wastewater. Weekly/bi-weekly measurements from three cities in France were analysed from February to September 2021. The concentrations of SARS-CoV-2 gene copies were normalised to the faecal-contributing population using simple sewage component indicators. To reduce the measurement error, a composite index was created to combine simultaneously the information carried by the simple indicators. The results showed that the regularity (mean absolute difference between observation and the smoothed curve) of the simple indicators substantially varied across sampling points. The composite index consistently showed better regularity compared to the other indicators and was associated to the lowest variation in correlation coefficient across sampling points. These findings suggest the recommendation for the use of a composite index in wastewater-based epidemiology to compensate for variability in measurement results. HIGHLIGHTS: SARS-CoV-2 RNA quantification in wastewater shows high variability and need to be normalized. The performance of various normalized indicators, including a composite index was assessed via two criteria: regularity and correlation with the incidence rate. The composite index showed the best performance. Except for the F-specific RNA bacteriophage normalisation index, correlation of all indicators with the incidence rate was substantial. Graphical Abstract